A survey of groundwater quality in Tulum region, Yucatan Peninsula, Mexico - Renaud Saint-Loup; Théo Felix; Axaycatl Maqueda; Arnulf Schiller; Renard, Philippe (My University, 2018)
The city of Tulum, in the state of Quintana Roo (Mexico) depends almost exclusively on groundwater for water supply. The groundwater is exploited from a coastal aquifer which contains a karst network that is considered as one of the largest ones on earth. Given the nature of karst aquifers, the whole area is very sensitive to contaminants and bacteria transport, because flow paths, residence time and degradation rates differ significantly from what can be observed in the porous aquifer. The present study focuses on isotopes (18O and 2H), dissolved ions’ concentration and Escherichia coli (E. coli). The result of our survey points out the anthropic impact on groundwater quality. Furthermore, the chloride concentrations illustrate the influence of seawater mixing and geological heterogeneity over the study area. Due to an exponential growth of the tourism industry, the needs in terms of water supply and water treatment increase significantly. Tulum is a coastal city, facing a coral reef and is bordered by the Sian Ka’an biosphere reserve, therefore, an environmental issue is added to the sanitary issue, both being the basis of the local economic development. Our results show that E. coli remains a major issue, as several samples tested were contaminated, in particular those in the city center. Ions’ survey shows an anthropic impact through nitrate, phosphate and fluoride concentrations, but the obtained values are not alarming. Considering the saline intrusion, chloride concentrations indicate that the area below the Tulum city center seems to be less permeable (and maybe less karstified) than the surrounding areas, as groundwater is less subject to seawater mixing than other sampling sites at similar distance to the coast.